B2.5-Eunomia simulations of Magnum-PSI detachment experiments: II. Collisional processes and their relevance. (26th November 2021) - Chandra, R; de Blank, H J; Diomede, P; Westerhof, E
Abstract: Detachment is achieved in Magnum-PSI by increasing the neutral background pressure in the target chamber using gas puffing. The plasma is studied using the B2.5 multi fluid plasma code B2.5 coupled with Eunomia, a Monte Carlo solver for neutral species. This study focuses on the effect of increasing neutral background pressure to the plasma volumetric loss of particle, momentum and energy. The plasma particle and energy loss almost linearly scale with the increase of neutral background pressure, while the momentum loss does not scale as strongly. Plasma recombination processes include molecular activated recombination (MAR), dissociative attachment, and atomic recombination. Atomic recombination, which includes radiative and three-body recombination, is the most relevant plasma process in reducing the particle flux and, consequently, the heat flux to the target. The low temperature where atomic recombination becomes dominant is achieved by plasma cooling via elastic H + −H2 collisions. The transport of vibrationally excited H2 molecules out of the plasma serves as an additional electron cooling channel with relatively small contribution. Additionally, the transport of highly vibrational H2 has a significant impact in reducing the effective MAR and dissociative attachment collision rates and should be considered properly. The relevancy of MAR and atomic recombination occupy separate electron temperature regimes, respectively, at T e = 1.5 eV and T e = 0.3 eV, with dissociative attachment being relevant in the intermediary. Plasma cooling via elastic H + −H2 collisions is effective at T e ≤ 1 eV.